Endothelium-dependent relaxation in response to poly-L-arginine in canine coronary arteries: implications about hyperpolarization as a mechanism of vasodilatation - Evora,Paulo R. B. (2003)
OBJECTIVE: To study the mechanism by which poly-L-arginine mediates endothelium-dependent relaxation. METHODS: Vascular segments with and without endothelium were suspended in organ chambers filled with control solution maintained at 37ºC and bubbled with 95% O2 / 5% CO2. Used drugs: indomethacin, acetycholine, EGTA, glybenclamide, ouabain, poly-L-arginine, methylene blue, N G-nitro-L-arginine, and verapamil and N G-monomethyl-L-arginine. Prostaglandin F2á and potassium chloride were used to contract the vascular rings. RESULTS: Poly-L-arginine (10-11 to 10-7 M) induced concentration-dependent relaxation in coronary artery segments with endothelium. The relaxation to poly-L-arginine was attenuated by ouabain, but was unaffected by glybenclamide. L-NOARG and oxyhemoglobin caused attenuation, but did not abolish this relaxation. Also, the relaxations was unaffected by methylene blue, verapamil, or the presence of a calcium-free bathing medium. The endothelium-dependent to poly-L-arginine relaxation was abolished only in vessels contracted with potassium chloride (40 mM) in the presence of L-NOARG and indomethacin. CONCLUSION: These experiments indicate that poly-L-arginine induces relaxation independent of nitric oxide.